Archaeology in Asia Minor - Mellink, Machteld J.
Palaeolithic Sites: Mağracik, Karain, Maraş; Chalcolithic and Bronze Age Sites: Kültepe, Horoztepe, Boğazköy, Karahüyük, Konya Plain, Hacılar, Höyücek, Bayındır, Commagene; Iron Age and Classical Sites: Boğazköy, Ankara, Karatepe, Commagene, Zincirli-Yesemek, Islahiye District, Misis-Mopsuehestia, Konya-Yunus, Xanthos, Hierapolis, Side, Perge, Miletus, Klaros, Sardis, Pergamon, Dascylium, Ömerli, Nicomedia, Adapazari.